Pengelolaan berbasis Masyarakat Sasi Laut Folley dan Dinamika Pengelolaan Berbasis Masyarakat - Fevi Rahma Dwi Putri; Arif Satria; Saharuddin Saharuddin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Abstract: Indonesia is currently experiencing a decline in the quantity and quality of natural resources. The main cause is due to excessive use of natural resources and destructive behavior without responsibility of various parties. Mitigation measures that have been taken only benefit certain parties. An appropriate management model that is beneficial for all parties is needed. Community based management (CBM) such as the management of Sasi Laut in Kampung Folley, West Papua is one of the models considered appropriate to apply. Sasi as a tradition, is thought to undergo many changes. The aim of this study is to analyze the dynamics of the management of Kampung Folley Sea Sasi and its impact on strengthening management. The results of this study indicate that there is a management dynamics that involves five momentum changes, namely the formation of the village, the intervention of the role of religion, the introduction of technology, the involvement of external parties and the establishment of regulations for Water Conservation Area. The management elements that have changed are territorial boundaries, regulations, authority holders, rights, sanctions, and monitoring due to internal and external factors. The management dynamics that occur are leading to the strengthening of Sasi Laut management.